The Inspiring Lecturers of Teaching English - Alfisah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
Mastering English is very important for the students, especially because of English, is necessary as a means of getting knowledge. Moreover, English can help the learners to make a change for the country and also his/her life. English is an official language or chosen language as in many schools across the globe. The competence of teachers should be improved. English learners in the modern language classroom often learn through techniques drawn from a variety of methods/approaches in such a way to make a teaching and learning become successful and meaningful. The teachers may select techniques from various approaches according to the different needs of their learners with only a single purpose to create bright students and qualified human resources.